2013
DOI: 10.1159/000355356
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Depression and Anxiety Correlate with the Degree of Hirsutism

Abstract: Background: Hirsutism has a negative impact on women's quality of life. The relation between quality of life, anxiety, depression and the level of hairiness has not been described. Aims: To investigate the correlations between the levels of hairiness, quality of life, anxiety and depression. Methods: 200 patients from Malmö, Örebro and Uppsala, who had been in contact with the clinics for problems with excessive hair growth, were invited to answer a self-administered questionnaire including sociodemographic qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 32 publications
4
34
1
2
Order By: Relevance
“…Hyperandrogenic skin symptoms such as acne and hirsutism are associated with considerable impairment of quality of life and adverse psychological impact [4,5]. Pharmacological treatment of these symptoms aims to reduce the level of circulating androgens and inhibit their effect at tissue level.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Hyperandrogenic skin symptoms such as acne and hirsutism are associated with considerable impairment of quality of life and adverse psychological impact [4,5]. Pharmacological treatment of these symptoms aims to reduce the level of circulating androgens and inhibit their effect at tissue level.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Acne is a less prevalent and less specific marker of elevated androgens (hyperandrogenism) and is present as a symptom in approximately 15% of women with PCOS [3]. Both hirsutism and acne can significantly and negatively impact on quality of life and cause anxiety and depression [4,5]. Female androgenic alopecia affects approximately 35% of women with PCOS and can occur either in isolation (rarely) or in association with other skin symptoms of hyperandrogenism [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is a well-documented impact on psychological well-being, often manifesting in psychiatric problems ranging from depression to anxiety 2 . Several studies have examined the relationship between psychiatric morbidity and skin diseases [3][4][5][6][7] . Psoriasis is associated with psychological disorders with sexual and sleep complaints being the most prevalent 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, of the few BDD respondents in Study III who agreed to a diagnostic interview, three of seven screened falsely positive on the BDDQ for this very reason (they had noticeable appearance 'dlaws' caused by their dermatologic disease). In Swedish women with hirsutism, levels of depression (16%) and anxiety (37%) as dedined by HADS ≥11 were closer to the levels reported by the BDD respondents than by the non-BDD respondents in Study III (Ekbäck et al, 2013). Both hirsutism and acne patients may theoretically screen falsely positive for BDD, and thus may, in part, be included in the BDD respondents.…”
Section: Capturing Bdd In Dermatology Patientsmentioning
confidence: 63%
“…A large study of dermatology out-patients from 13 European countries (n=3 600) reported depression in 10% and anxiety in 17% of the patients based on a HADS cut-off value of 11 (Dalgard et al, 2015). In a Swedish sample of women with hirsutism (n=132) (Ekbäck et al, 2013), anxiety was found in 37% and depression in 16% of the patients (HADS ≥11), rates that are similar to the rates in BDD respondents in Study III (those dindings are discussed in section 5.2.4).…”
Section: Emotional Suffering and Psychosocial Handicap Associated Witmentioning
confidence: 99%